Comparing The Effectiveness of Mindfulness-Based Therapy and Paradoxical Treatment on Rumination in Adolescents with Social Anxiety Symptoms - Nurollahi, Atefeh; Shahabizadeh, Fatemeh; Nasri , Maryam (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective:  This study aimed to compare the effectiveness of Mindfulness-Based Therapy (MBT) and Paradoxical Treatment (PT) in reducing rumination and associated symptoms in adolescents with social anxiety disorder (SAD).Methods and Materials: The study employed a quasi-experimental design with pretest-posttest and two-month follow-up across two experimental groups and one control group. Sixty adolescents aged 12-18 years with diagnosed SAD were selected through purposive sampling and randomly assigned to MBT, PT, or control groups (20 participants each). Participants completed self-report measures of rumination and depression at three stages: pretest, posttest, and follow-up. The MBT group received seven weekly 90-minute sessions based on Kabat-Zinn’s mindfulness framework, while the PT group received seven weekly 90-minute sessions focused on paradoxical intention strategies. Data were analyzed using repeated measures ANOVA, with Bonferroni post-hoc tests to explore differences between groups and across time points.Findings: The repeated measures ANOVA indicated significant within-group effects for both brooding (F(1.24, 190.59) = 30.87, p < 0.001, η² = 0.35) and reflection (F(1.29, 254.37) = 64.45, p < 0.001, η² = 0.53). Interaction effects between the test stages and group were also significant for both brooding (F(2.49, 74.03) = 11.99, p < 0.001, η² = 0.30) and reflection (F(2.58, 59.34) = 15.04, p < 0.001, η² = 0.35). Post-hoc tests revealed significant reductions in rumination and depression for both MBT and PT groups compared to the control group, with no significant difference between the interventions.Conclusion: Both MBT and PT are effective in reducing rumination and depression in adolescents with SAD, providing sustained therapeutic benefits over time.